2011
DOI: 10.1007/s12010-011-9293-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bleached Wool with Trans-Glutaminases to Enhance Tensile Strength, Whiteness, and Alkali Resistance

Abstract: Trans-glutaminases is known as a cross-linking enzyme for proteins. Wool is a proteinous fiber conventionally is treated through several processes to obtain the desirable characteristics. Bleaching is also one of the most important processes usually carried out by using an oxidizing agent in a conventional method. The tensile strength of wool yarns was reduced as a consequence of oxidative bleaching. Here, with the help of microbial trans-glutaminases (m-TGases), a novel bleaching process was disclosed in a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The introduction of additional crosslinks into the keratin network by the use of enzymes represents an approach to compensate for the loss of tensile strength caused by peptidase-catalyzed hydrolysis. Several studies indicated that keratin fibers crosslinked by microbial transglutaminase maintain higher fabric strength after (1) proteinase treatment (Cortez et al 2004; Du et al 2007), (2) repeated washing cycles with proteinase-containing detergents (Cortez et al 2005), or (3) bleaching with hydrogen peroxide (Montazer et al 2011) as compared to the corresponding fibers without enzyme treatment. Furthermore, transglutaminase has been employed to graft casein (Cui et al 2011), gelatin (Cui et al 2009), and silk proteins (Cortez et al 2007) onto wool yarns, generating products with improved physicomechanical properties such as increased tensile strength and higher smoothness.…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…The introduction of additional crosslinks into the keratin network by the use of enzymes represents an approach to compensate for the loss of tensile strength caused by peptidase-catalyzed hydrolysis. Several studies indicated that keratin fibers crosslinked by microbial transglutaminase maintain higher fabric strength after (1) proteinase treatment (Cortez et al 2004; Du et al 2007), (2) repeated washing cycles with proteinase-containing detergents (Cortez et al 2005), or (3) bleaching with hydrogen peroxide (Montazer et al 2011) as compared to the corresponding fibers without enzyme treatment. Furthermore, transglutaminase has been employed to graft casein (Cui et al 2011), gelatin (Cui et al 2009), and silk proteins (Cortez et al 2007) onto wool yarns, generating products with improved physicomechanical properties such as increased tensile strength and higher smoothness.…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…Model tapestries, modern surrogates, have also been used as a means of reproducing typical damage under accelerated ageing regimes, although it has so far proved impossible to recreate the extreme damage seen in historic tapestries (Duffus, 2013). Much research on the physical and chemical properties of yarns and fibres used in textile manufacture has been carried out (Dubro, 1987;Montazer et al, 2011;Periolatto et al, 2011), but processing, spinning, and dyeing would have affected the individual properties of yarns used in the past. The research reported here aimed to seize the valuable opportunity of a contemporary major tapestry weaving project, the creation of a set of tapestries for Stirling Castle, to capture information on the properties of the wool yarns used in the weaving.…”
Section: 'Monitoring Of Damage To Historic Tapestries' (Modht)mentioning
confidence: 99%
“…There have been several reports on the application of m‐TGase on wool . In our previous study, we used hydrogen peroxide as a bleaching agent and m‐TGase as an after‐treatment process to revenge the negative influence of alkali bleaching process . There is no report, however, on the application of m‐TGase on the depigmented wool yarns.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the optimum conditions for m‐TGase treatment on wool is 20% m‐TGase w/w (weight of m‐TGase to weight of goods) at 37°C in pH 9–10 with L:G (liquor‐to‐goods ratio) = 40:1 . The same conditions were adopted in this research for depigmented wool treatment with m‐TGase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation